Deformation prediction of composite specimens subjected to three-point bending tests - Monte, Sara M. C.; Infante, Vírginia; Moleiro, F.; Madeira, J. F. A. (My University, 2015)
A computational and experimental study was carried out in order to determine the deformations of specimens made in laminated composite material when subjected to three - point bending test. The specimens were produced using unidirectional carbon fiber prepreg with different aspect ratios and different lamination schemes. The experimental deformations of the bending tests were obtained using an innovative method called digital image correlation. At the computational level, two models were compared: the first developed in ANSYS and the second, not available in any commercial program, developed by MOLEIRO, 2010.The latter presents a mixed Layerwise formulation that assumes displacements and transverse stresses as independent variables, and therefore is able to a priori fulfill the interlaminar continuity C^0 of tranverse stresses and displacements. ANSYS model uses a solid element, in the laminated structural version, and assumes a displacement formulation. It was concluded that the ANSYS model results are more similar to the experimental results of longer specimens and the Layerwise mixed model results are more similar to the experimental results of shorter specimens.
Keywords: Three-point bending test; Digital image correlation; Layerwise finite element modelling